(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This thesis examines the lexical-semantic classification of technical terms in English, Uzbek and Russian. Technical terminology is a special layer of vocabulary that serves professional communication and reflects the conceptual system of science, engineering and technology. The purpose of the thesis is to identify the main lexical-semantic groups of technical terms in the three languages and to explain their similarities and differences. The study is based on descriptive, comparative and semantic methods. The findings show that technical terms may be classified according to the concepts they denote, including devices, processes, materials, properties, measurements, systems, operations and professional fields. English terminology is characterized by compactness and wide use of international terms, Russian terminology demonstrates a developed derivational and conceptual structure, while Uzbek terminology combines native, borrowed and translated units. The thesis concludes that lexical-semantic classification is important for translation, terminology standardization, technical education and multilingual communication.